Efeito do laser de baixa intensidade no processo de cicatrização muscular e células satélites - Nogueira, Daniela Guimaraes Moraes (2006)
Low-level laser therapy (LLLT) is frequently used in clinics as a physiotherapeutic resource to repair muscle. Nevertheless, there is no scientific evidence regarding its action, dosimetry and therapeutic effectiveness. The objective of this study was to observe changes caused by gallium arsenide laser irradiation (660m) on the gastrocnemic muscle in rats following surgical injury, using satellite cell proliferation as the parameter. The study was conducted using 36 Wister strain rats, 250g average weight, divided into two groups of 18: control group (C) and laser group (L). The animals in both groups underwent surgical injury to the right gastrocnemic muscle. Within a short time of wounding, laser treatment with a 2j/cm2 dose was initiated in the laser (L) group. The two groups were divided into C1, C2 and C3, L1, L2 and L3 sub-groups respectively. The animals in both sub-groups were sacrificed at separate post-operative periods, 24, 48 hours and 7 days respectively. The injured muscle fragments and adjacent areas were removed and histopathological analysis performed. Inflammatory cells, fibroblasts, vascularization and collagen depositions were observed. There was no significant difference between the control and laser therapy groups during the observation period. On immunohistochemical evaluation using a MyoD1 stain, a statistically significant difference (p<0.05) was observed between the control and laser therapy groups with relation to the proliferation of satellite cells. This study suggests that laser therapy accelerates muscle repair in surgically injured rats following the observation of increased satellite cell proliferation in the early stage of the regeneration process.